Peningkatan Desain Antarmuka Game Fallout 4 dengan User Created Mods menggunakan Metode Human Centered Design (HCD) - Andi Aderian Arhadianto; Aryo Pinandito; Prima Zulvarina (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The improvement of Fallout 4 game interface design with user created mods using human centered design approach. The problem to be solved is how the efficiency and effectiveness of the Fallout 4 game interface in initial and final conditions with the obtained comparison value of efficiency (initial: default, final: modified with user-created content). The aim is to explain the improvement of time efficiency in exploring the interface in the Fallout 4 game using usability testing using an interface that has been modified based on Human Centered Design. The working conclusion is that there is a difference in the feeling obtained from the data analysis. The efficiency test value shows that the use of the modified interface is more efficient than the unmodified interface. This indicates that the improvements made to the interface are effective in increasing usability and ease of use for users.